An African Art Re-Discovered: New Revelations on Sword Manufacture in Dahomey - Ron Lawrence Anderson; Filomena Salvemini; Maxim Avdeev; Vladimir Luzin (Heritage)
Antique swords from the pre-colonial West African kingdom of Dahomey are aesthetically unique, but they also have many design features inspired by swords from Europe, the Islamic world and elsewhere. As the kingdom was famous for importing luxury European objects, this study aimed to pinpoint evidence of Dahomean sword composition and manufacture to determine scientifically whether they were being made in Dahomey, or imported. An inter-disciplinary team made up of historical archaeologists and neutron scientists examined six 19th century Dahomean swords, using a non-invasive multi-methodological approach based on neutron tomography, powder diffraction full pattern analysis and diffraction residual stress measurements. The findings suggest that, despite their foreign design influences, not only were these striking heritage objects made in Africa, they may also have been likely made from locally smelted iron–something that contradicts the assumptions of the few existing historical reports. This has important implications for studies on the kingdom, and also helps to further the long-standing debate surrounding European iron imports—not just within Dahomey, but throughout the wider West African region.